2022
DOI: 10.1002/pat.5612
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a polycarboxylate superplasticizer modified by sodium hypophosphite

Abstract: A sodium hypophosphite (SHP) modified polycarboxylatesuperplasticizer (P-PCE) was synthesized successfully and the synthesis parameters were optimized through orthogonal experiment. Gel permeation chromatography (GPC), X-ray photoelectron spectroscopy (XPS), 31 P magic spinning nuclear magnetic resonance ( 31 P MAS NMR) spectroscopy and elemental analysis measurements were used to characterize the molecular structure of P-PCE. Effects of P-PCE on the dispersing performance of cement paste were systematically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…However, the current machine-made sand on the market often has the problem of unstable clay content. A large number of scholars at home and abroad have studied the effect of clay on the performance of the polycarboxylic acid water reducer (PCE) and found that the layered structure of clay easily makes the conventional PCE fail due to intercalation and adsorption into the layered structure of clay [4][5][6]. It is of great significance to develop a clay-resistant polycarboxylic acid water reducer that is not easily adsorbed to the layered structure of clay.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current machine-made sand on the market often has the problem of unstable clay content. A large number of scholars at home and abroad have studied the effect of clay on the performance of the polycarboxylic acid water reducer (PCE) and found that the layered structure of clay easily makes the conventional PCE fail due to intercalation and adsorption into the layered structure of clay [4][5][6]. It is of great significance to develop a clay-resistant polycarboxylic acid water reducer that is not easily adsorbed to the layered structure of clay.…”
Section: Introductionmentioning
confidence: 99%